Methyl lucidone induces apoptosis and G2/M phase arrest via the PI3K/Akt/NF-κB pathway in ovarian cancer cells. (1st January 2020) - Yoon, Jae-Hwan; Shin, Jong-Woon; Pham, Thu-Huyen; Choi, Youn-Jin; Ryu, Hyung-Won; Oh, Sei-Ryang; Oh, Jae-Wook; Yoon, Do-Young
Abstract: Context: Methyl lucidone (ML) from the dried fruit of Lindera erythrocarpa Makino (Lauraceae) exhibits cytotoxic effects in various cancer cell lines. However, its effects on ovarian cancer cells remain unknown. Objective: This study evaluates the mechanism of ML-induced apoptosis, cell cycle distribution in ovarian cells. Materials and methods: The cytotoxic effect of ML (2.5–80 µM) on OVCAR-8 and SKOV-3 cells was evaluated by MTS assay for 24 and 48 h. Apoptosis and cell cycle arrest were analysed by flow cytometry. PCR, western blot analyses were performed to examine the related signalling pathways. Results: ML induced significant cellular morphological changes and apoptosis in ovarian cancer cells, leading to an antiproliferative effect (IC50 = 33.3–54.7 µM for OVCAR-8 and 48.8-60.7 µM for SKOV-3 cells). Treatment with ML induced cleavage of caspase-3/9 and PARP and release of cytochrome c from the mitochondria. Moreover, ML downregulated the expression of Bcl-2 and Bcl-xL and induced cell cycle arrest in the G2 /M phase. Additionally, ML suppressed the expression of cyclin-A/B and promoted that of the cyclin-dependent kinase inhibitors p21 and p27. The expression of death receptors was not altered. Interestingly, ML also inhibited the activity of PI3K/Akt and NF-κB. Discussion and conclusions: ML caused G2 /M phase arrest and apoptosis in ovarian cancer cells by activating intrinsic apoptotic pathways and suppressing the PI3K/Akt survival pathway. ML may be a potential anticancer agent to suppress ovarian cancer proliferation; thus, to improve the survival rate of cancer patients.